Advances in the Treatment of Acute Myeloid Leukemia: Implications for Low- and Middle-Income Countries - Michelle Morcos-Sandino; Sofia Isabel Quezada-Ramírez; Andrés Gómez-De León (Biomedicines)
Acute myeloid leukemia (AML) presents a significant global health challenge due to its aggressive behavior and mortality rates. Traditionally, AML treatment has relied on intensive chemotherapy—anthracyclines and cytarabine. However, recent breakthroughs in targeted therapies are transforming clinical practices. This review examines current treatment strategies, including breakthrough therapies. Also, a global perspective on AML management includes the disparity in treatment availability, particularly the difficulties faced by low- and middle-income countries due to the high cost and restricted access to novel therapies.